2017
DOI: 10.1177/0363546517744313
|View full text |Cite
|
Sign up to set email alerts
|

Age Influences Biomechanical Changes After Participation in an Anterior Cruciate Ligament Injury Prevention Program

Abstract: ACL prevention programs may be more effective if administered early in an athlete's career, as younger athletes may be more likely to adapt new biomechanical movement patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 31 publications
0
37
0
1
Order By: Relevance
“…Three studies examined the effects of balance training [63, 67, 68], two studies examined resistance training [62, 63], while one study examined the effects of dynamic core-stability training [66], and one other study examined perturbation-enhanced plyometric training [69]. Two studies examined the effects of the Oslo neuromuscular warm-up protocol [72, 73], two studies examined the core position and control (Core-Pac) warm-up intervention [74, 75], and two studies examined FIFA’s Medical Assessment and Research Centre 11+ (F-MARC 11+) soccer-specific injury-prevention warm-up [70, 71] interventions on COD biomechanics. Eleven of the 22 studies failed to include a control group (Tables 1, 2, 3, 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies examined the effects of balance training [63, 67, 68], two studies examined resistance training [62, 63], while one study examined the effects of dynamic core-stability training [66], and one other study examined perturbation-enhanced plyometric training [69]. Two studies examined the effects of the Oslo neuromuscular warm-up protocol [72, 73], two studies examined the core position and control (Core-Pac) warm-up intervention [74, 75], and two studies examined FIFA’s Medical Assessment and Research Centre 11+ (F-MARC 11+) soccer-specific injury-prevention warm-up [70, 71] interventions on COD biomechanics. Eleven of the 22 studies failed to include a control group (Tables 1, 2, 3, 4).…”
Section: Resultsmentioning
confidence: 99%
“…One study has shown promising results regarding the effectiveness of dynamic core stability training on COD knee joint loading [66], but further research is needed to definitively confirm the efficacy of this method. Perturbation-enhanced plyometric training [69], the F-MARC 11 + [70, 71], Oslo Neuromuscular warm-up protocol [72, 73] and resistance training [62, 63] are ineffective in reducing COD knee joint loads, whereas conflicting findings have been observed for the Core-Pac [74, 75], and mixed programme training interventions [53, 58–61, 65]. More research is required around plyometric-related interventions for the development of safer cutting mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the overall rate of injury among this group of players was comparable to those in the senior handball team (Olsen et al, 2006). Thompson-Kolesar et al (2017) investigated the effects of FIFA Medical and Research Center (F-MARC) 11+ injury prevention warm-up program on biomechanical risk factors for ACL injury among pre-adolescent and adolescent female soccer players. Each age group was divided into two groups; intervention (received F-MARC 11+ injury prevention warm-up program in 15 sessions for 7-8 weeks (2 sessions per week)) and control (did not received any program).…”
Section: Discussionmentioning
confidence: 99%
“…Two types of kinetic chain play a major role in the mechanism of DKV, namely top-down (proximal origin) and bottom-up (distal origin) kinetic chains (Jamaludin et al, 2020). A top-down kinetic chain occurs when the hip and trunk muscles alter the distal joints' kinematic patterns (Snyder et al, 2009). On the contrary, a bottom-up kinetic chain involves the influence of ankle musculature and foot structures on knee joint motions (Khamis & Yizhar, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation